Socialismo democrático : algunas alternativas para una economía política (notas para una conferencia en Cuba, Enero de 2009) - Offe, Claus; Capriles, Iván; Morcillo Laiz, Álvaro (El Colegio de México, 2014)
The holders of political power may choose among the myriad of institutional possibilities that exist between capitalism and socialism. After explaining why any system of production is mixed, this essay explores both why markets are frequently considered preferable to other arrangements and which are the “simple” wrongs associated with capitalist market economies. Among these “simple” wrongs, we find markets’ tendency to self-subversion, to permeate the whole of social life, and to inflict damage when it is permitted to markets to encompass the factors of production, like labor, natural resources, and money. Despite these “simple” wrongs, democratic socialists and social democrats believe that the political power mobilized within liberal democracies can cope with these side-effects by resorting to instruments like anti-trust legislation, market-constraining policies, and to the protection of the factors of production. Finally, the essay explains why social democrats and democratic socialists believe that liberal democracy, with its emphasis on liberty and equality, on the one hand, and on representation, contestation, and accountability, on the other, is the institutional arrangement that can best cope with the inherent pathologies of capitalist market societies